The Role of Distributive Leadership of Headmasters In Selected Primary School, Ampang, Selangor. - NEE, LEONG FERN; ABDULLAH, ZURAIDAH (EARR (Educational Administration Research and Review), 2022)
The main purpose of this study is to investigate the role of distributive leadership (DL) of headmasters in selected primary school at Ampang, Selangor. DL is an important strategic approach which leads to quality education. Headmasters’ distributive roles have four dimensions includes shared mission, vision and goals, school culture, spontaneous collaboration and shared responsibilities. The research design of this study is a quantitative method, and questionnaire is used to collect the data. There are N=351 primary teachers from two type’s school categories which are Sekolah Kebangsaan (SK) and Sekolah Jenis Kebangsaan Cina (SJKC) were selected by random sampling. Findings show that there is a high level of DL (M=3.74, SD=.59) demonstrated by headmasters. This study clearly shows Malaysia practices a bureaucratic system in education. Results also show that headmasters' leadership style influence the school managements which is lead to students’ learning outcomes. These studies have implications for administrator, teachers, students and education policymaker. The results of this study provide ideas to policymakers to take action to enact the appropriate module with school context. In brief, headmasters play distributive roles in enhancing teachers’ development and students’ improvement to realise an effective school.